معالجة المخلفات التصنيعية لثمار الحمضيات بهدف إنتاج الكحول الإيتيلي والكتلة الحيوية - ياسين, مفيد (Latakia University Journal -Medical Sciences Series, 2019)
تنمية خميرة الـ Saccharomyces cerevisiae على مخلفات تصنيع ثمار الحمضيات المنتجة في سورية تمثل إحدى الإمكانيات التي يمكن بواسطتها إنتاج الكحول الإيتيلي بمردود 30-47%, وبروتين الكتلة الحيوية بزيادة من (3-5) مرات, وتحسين في صفاتها الكمية والحسية. يعتبر هذا الوسط المتخمر الناتج عالي القيمة بمحتواه في البروتين وألياف البكتين والليمونئيدات والفلافونئيدات التي تعتبر عوامل حماية كيميائية التي يمكن استخدامها كمنتجات تغذوية لدى الإنسان أو أعلاف حيوانات. Saccharomyces cerevisiae cultivation on citrus fruit waste can present a possibility for up-grading the waste obtained at citrus juices production in Syria. By cultivating Saccharomyces cerevisiae, the distillated ethanol ratio of the fermented medium was (30-47%) and protein of biomass was increased by 3-5 times and its quantitative and qualitative have improved Thus, fermented media with its high content of proteins, pectin fibers, limonoides and flavnoides acting as chemoprotectors agents could be used as nutrition products for human and feed for animals